ANALISIS PROFITABILITAS USAHATANI BAWANG MERAH BERDASARKAN MUSIM DI TIGA KABUPATEN SENTRA PRODUKSI DI INDONESIA - Haris F. Aldila; Anna Fariyanti; Netti Tinaprilla (Universitas Sebelas Maret, 2015)
The objectives of this research are (1) to analyze the characteristics of farmers and the performance of shallot farming and (2) to analyze the profitability of shallot farming in production centers in Java. The research was conducted in Cirebon, Brebes, and Tegal regency with the number of respondents each of 40 farmers. Farm profitability level indicated by R/C ratio in every season (rainy season, first dry season and second dry season) during 2013/2014. The results showed that shallot farming in Cirebon, Brebes, and Tegal feasible and profitable to cultivate in every season. Farmers in Cirebon had the biggest gain in the second dry season of Rp 47 million per hectare with R/C of 1.65. Farmers in Brebes had the biggest gain in the first dry season amounted to Rp 23 million per hectare with R/C of 1.42. Farmers in Tegal had the biggest gain in the rainy season of Rp 31 million per hectare with R/C of 1.48.